Value stream mapping in a discrete manufacturing: A case study - Anup Prabhakarrao Chaple; Balkrishna Eknath Narkhede (International Journal of Supply Chain Management, 2017)
The purpose of this paper is to apply value stream mapping (VSM) for making improvement roadmap in a discrete manufacturing organization. This study provides an up-to-date, review of value stream mapping. A systematic methodology is presented in this paper for selecting product family and processes for improvements. A current state map is developed after critical observations, calculations, and analysis for identifying wastes in current system. The various tools of lean manufacturing are then discussed to establish improvement roadmap, which lead to future state mapping. The improvements evaluated on key performance indicators such as lead time, inventory reduction and increased value addition. In order to implement VSM in a discrete manufacturing organization, this study gives a complete overview of conducting value stream mapping study. The value stream mapping study reported is an original work of the authors which conducted in discrete manufacturing scenario represented by low volume with high variety products. With this context of complexity to develop value stream maps, the study is considered to be highly valuable.